Ilegal Fishing sebagai Ancaman Kedaulatan Bangsa - Amin Bendar (Perspektif Hukum, 2015)
Indonesia is the largest archipelagic state in the world where the sea area is larger than the mainland. The sea that seems to float island also contains marine wealth at its cranny like fish and other biota. A weak supervision toward the sea of Indonesia effects illegal fishing massively done by foriegn fishery corporations from neighbouring states, so that the illegal fishing makes budget state loss 300 trillion each year. More shockingly, the catched fish are brought to their country and then are exported to Indonesia at the cheap price, so threatens the price determained by local fishermen. An effort to stop the illegal fishing in Indonesia is that the government explicitly utilizes Act Number 45 Year 2009 about Fishery, Minister Regulation Number 2 Year 2015 about Tiger Trawl Usages, and other Acts, Government Regulation, and President Decision. Otherwise, based on the 1945 Constitution of Republic of Indonesia, the 1975 Djuanda's Declaration, UNCLOS III Year 1982 about archipelagic concept of Indonesia, and Exclusively Economic Zone, the Government legally punishes actors of the illegal fishing by burning and sanking their ships to assert sovereignty of Indonesia. The Government’s legal action doesn't break the law, because it is in accordance with the national and international law.